Why people use social media: An investigation of engagement on an all-service platform - Steven Bauer; Fang Tian (Cogent Business & Management, 2024)
This study provides the first investigation of the complete group of variables in the expanded theory of uses and gratifications on consumer engagement in an all-service social media platform. Consumer engagement is measured both from a psychological state and behavioral perspective, an approach which is important since the antecedent variables in uses and gratifications theory have both psychological and behavioral manifestations. A survey is conducted in Mainland China on WeChat with 805 respondents. Antecedent variables and consumer engagement are measured using previously validated scales. Regression analyses find that the antecedent variables of entertainment, integration/social interaction, personal identity, information, remuneration, and empowerment are significantly associated with consumer engagement on WeChat. Age and gender relationships are also explored in correlation and regression analyses, with associations strongest among males and older groups. The results give added support to the relevance of the uses and gratifications theoretical framework.
Keywords: 650; Social media marketing; consumer behavior; consumer psychology; customer experience; customer insight; marketing communication